Exploring Employability Competencies in Construction Trades: A Comparative Analysis of Bricklaying/Block Laying and Concreting Graduates in Diverse Specializations in Gombe State, Nigeria - V., Apagu, V.; A., Baba; T., Abba, A. (Mikailalsys Journal of Advanced Engineering International, 2024)
The purpose of this study was to Explore the Employability Competencies in Construction Trades: A Comparative Analysis of Bricklaying/Block Laying and Concreting Graduates in Diverse Specializations in Gombe State, Nigeria. The study was guided by three research questions and three null hypotheses guided the study. The study's population comprised 85 respondents, including 21 administrators, 48 teachers, and 16 building supervisors, making sampling unnecessary due to the manageable size of the population. Data collection utilized a structured questionnaire titled "Perceived Employability Competencies Questionnaire (PECQ)," specifically designed by the researchers to align with the research questions. The questionnaire featured two sections, A and B, and underwent face validation by three experts in the Department of Technology Education at Modibbo Adama University, Yola, Adamawa State. The instrument demonstrated a high reliability coefficient of 0.83, determined through Cronbach Alpha. Data analysis for the research questions involved calculating mean and standard deviation, while ANOVA was employed to test null hypotheses at a 0.05 level of significance. Findings of the study revealed among others that 24 employability competencies in bricklaying/block laying possessed and required by Graduate Students of BBC trade. 15 employability competencies in concreting were possessed and required by Graduate Students of BBC trade. It is recommended that Students of BBC trade should be exposed to activities that involve bricklaying and block laying works so that the students can improve their competencies when performing blocklaying work. And administrators of Technical Colleges should ensure that materials for concrete practice are provided to ensure adequate skill acquisition during practical lessons.